Biomass ash characterization, fusion analysis and its application in catalytic decomposition of methane. (1st February 2021) - Assad Munawar, Muhammad; Hussain Khoja, Asif; Hassan, Muhammad; Liaquat, Rabia; Raza Naqvi, Salman; Taqi Mehran, Muhammad; Abdullah, Ali; Saleem, Faisal
Graphical abstract: Highlights: The characterization and ash fusion temperature of biomass ash (BFA/BBA) is investigated. The CeO2 modified BFA/BFA shows higher fusion temperatures. The physicochemical characteristics depict the suitability of BFA as a catalyst support. Co/BFA shows stable H2 production via CH4 decomposition for 330 min on stream. Abstract: The biomass utilization for power generation is one of the efficient pathways to reduce greenhouse gas emissions. However, the high ash formation in biomass fed power plants raises several concerns, especially ash handling and its utilization. In this study, the biomass ash characterization, ash fusion analysis and its utilization as a catalyst in methane (CH4 ) decomposition were systematically investigated. The biomass bottom ash (BBA) and biomass fly ash (BFA) were modified using laboratory synthesized CeO2 nanoparticles to enhance the fusion temperature. The BBA, BFA and modified CeO2 -BBA/BFA samples were characterized by ultimate analysis, X-ray diffraction (XRD), scanning electron microscopy (SEM), thermogravimetric analysis (TGA), Fourier-transform infrared spectroscopy (FTIR), and X-ray fluorescence (XRF) analysis to investigate the physicochemical properties and its suitability for the catalysis applications. The detailed characterization inferred that BFA has significant potential in improving the ash fusion temperature as well as suitable for catalysis of fuel processing due to the presence of metal oxides such as Fe2 O3, SiO2, CaO, Al2 O3 and its porous structure. Furthermore, the most suitable BFA was impregnated with cobalt (Co). Co loaded BFA was employed for CH4 decomposition at 700 °C for H2 production in a fixed bed reactor. The Co/BFA demonstrated a stable catalytic activity of more than 330 min on stream with optimum H2 yield of 30%. The direct employment of BFA as catalyst support shows potential in further catalytic applications and material applications.